Role of Social Media Marketing Activities in Influencing Customer Intentions: A Perspective of a New Emerging Era - Jamil, Khalid; Dunnan, Liu; Gul, Rana Faizan; Shehzad, Muhammad Usman; Gillani, Syed Hussain Mustafa; Awan, Fazal Hussain (Frontiers in Psychology, 2022)
The aim of this study is to explore the social media marketing activities and their impact on consumer intentions (continuance, participate, purchase). This study also analyzes the mediating roles of social identification and satisfaction. The participants in this study were experienced users of two social media platforms Facebook and Instagram in Pakistan. A self-administered questionnaire was used to collect data from respondents. We used online community to invite Facebook and Instagram users to complete the questionnaire in the designated online questionnaire system. Data were collected from 353 respondents and structural equation modeling was used to analyze the data. Results show that social media marketing activities have significant impact on intentions of users. Furthermore, social identification mediates the relationship of social media activities and satisfaction and satisfaction mediates the relationship of social media activities and intentions of users. This will help marketers how to attract customers develop their intentions. This is first novel study which used social media marketing activities to address the user intentions with the role of social identification and satisfaction in the context of Pakistan.